In situ corrosion testing of various nickel alloys at Måbjerg waste incineration plant. Issue 1 (10th October 2011) - Montgomery, M.; Hansson, A. N.; Jensen, S. A.; Vilhelmsen, T.; Nielsen, N. H.
Abstract The majority of waste in Denmark is disposed via waste to energy (WTE) incineration plants which are fabricated from carbon steel. However, due to the increasing corrosiveness of waste over the years, more corrosion resistant alloys are required. In Denmark, Inconel 625 (UNSN06625) is the weld overlay material currently being used to give improved corrosion resistance. In order to assess the use of alternative nickel alloys, test panels have been manufactured and inserted into Måbjerg waste incineration plant. Inconel 625 as a 50% weld overlay, two layered weld overlay and as a spiral weld overlay was exposed. Other nickel materials exposed were weld overlay Alloy 686, Alloy 50 and Sumitomo Super 625 coextruded tube. Exposure has been undertaken from 2003 to 2009 in the first pass and 2005–2009 in the second pass, and sections have been removed and investigated during this period. The composition of the deposits from the exposed waterwall panels was also analysed each time sections were removed. This paper will compare the various nickel alloys in the two areas and assess the results of the long‐term testing project.